Biomedical engineering research centre manpower report - Krishnan Shankar Muthu. (2008)
The report has four parts. In part 1, cardiovascular signal processing and analysis are covered. Cardiovascular diseases are of grave concern to society and new techniques are needed for improving the diagnosis of those diseases. Application of intelligent signal processing techniques is essential for efficient diagnosis of cardiac diseases. Development of telemedicine systems is essential for communicating medical information from a home or a remote place to the hospital for prompt care. The report summarises the development for new techniques for analysis of cardiovascular signals and diagnosis. Nonlinear modelling has been developed for simulation and compression of cardiovascular signals. Various techniques for analysis including autoregressive modelling and nonlinear analysis have been developed for analyzing cardiovascular and respiratory signals. A report on telemedicine, telecommunication and home healthcare system is given in part 2. This part also includes the design of a mobile telemedicine system with WLAN. In report 3, a fiber optic biosensor to monitor mutans streptococci activity in human saliva is described. Part 4 of this report outlines the research and developmental work carried in the area of biocomposite for biomedical applications in particular the field of orthopaedic, maxillo- facial and cranial surgery.